АPLICATION OF AUTOPLASME ENRICHED BY THROMBOCYTES (PRP-THERAPY), IN THE TREATMENT OF PATIENTS WITH HEAVY DISEASE WITH THE ACCOUNT OF METABOLIC ACTIVITY OF PERIPHERAL BLOOD CELLS - Swyryd-Dzyadykevuch, A. (The Ukrainian Scientific Medical Youth Journal, 2017)
The effectiveness of combined treatment of patients with acne has been evaluated by determining its effect on the metabolic activity of peripheral blood cells and the clinical course of dermatosis. We observed 38 patients with a mild acute illness (22 women and 16 men aged 76 to 33 years). The duration of the pathological process varied from 7 months to 12 years. The content of glycogen was determined in neutrophils, monocytes and thrombocytes by means of a PAS-reaction. Results of evaluation using the average cytochemical coefficient (CCC). It has been established that in patients with acute disease there is a decrease in the glycogen content in neutrophils in the CCC = 2.05 ± 0.05 (in the control of SCS = 2.31 ± 0.08; p <0.05). This suggests changes in the energy potential of individual leukocyte subpopulations. In the platelets, the content of glycogen remained within the limits of physiological oscillations - CSC = 1.39 ± 0.08 (in the control of CCC = 1.43 ± 0.09; p <0.05), however, there was a redistribution of the number of cells with varying saturations of the metabolite. It is proved to increase the effectiveness of treatment of such patients by using as a adjuvant agent an autoplasma enriched with platelets. Conclusions in acute illness there is a redistribution of energy possibilities of neutrophils and monocytes of peripheral blood. The content of glycogen in neutrophils and monocytes of peripheral blood in can serve as one of the criteria for the effectiveness of prescribed therapy. The use of an acute illness of an autoplasma enriched with platelets, increases the effectiveness of treatment due to its modulating effect on the metabolic activity of leukocytes and platelet peripheral blood.